1992
DOI: 10.1002/1097-0142(19920501)69:9<2258::aid-cncr2820690908>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma with two paraendocrine syndromes

Abstract: Simultaneous elevated levels of ectopic arginine vasopressin (AVP) and ectopic adrenocorticotropin (ACTH) were found in a patient with small cell carcinoma (SCC). The finding of one of these paraendocrine syndromes at the time of diagnosis is common; however, the simultaneous presence of both syndromes has been reported in the literature only on four occasions in the past 25 years. This is the only report in which elevated plasma levels of both hormones are documented in a patient who simultaneously fulfills t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It is noteworthy that thus far, there have been only nine reported cases wherein SCLC produced these two hormones simultaneously (2,(6)(7)(8)(9)(10)(11)(12)(13). According to these reports, the opposing effects of cortisol and ADH on renal sodium excre-tion sometimes complicate the diagnosis or result in a misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that thus far, there have been only nine reported cases wherein SCLC produced these two hormones simultaneously (2,(6)(7)(8)(9)(10)(11)(12)(13). According to these reports, the opposing effects of cortisol and ADH on renal sodium excre-tion sometimes complicate the diagnosis or result in a misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to these reports, the opposing effects of cortisol and ADH on renal sodium excre-tion sometimes complicate the diagnosis or result in a misdiagnosis. In addition, the presence of these paraneoplastic syndromes is indicative of a poor prognosis in SCLC patients, with overall survival of only 2-4 months (2,(6)(7)(8)(9)13).…”
Section: Introductionmentioning
confidence: 99%
“…Eight cases of SCLC [ 7 – 14 ] with dual SIADH and EAS described in literature are summarized in Table 2 . Six [ 7 , 9 11 , 13 , 14 ] out of eight cases did not have typical Cushingoid picture and presented with weight loss and SAME. We notice that dual SIADH and EAS in SCLC can be simultaneous or sequential with the latter carrying worse prognosis and shorter life expectancy compared to simultaneous disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinically apparent Cushing's syndrome is less common and the simultaneous presence of SIADH and ectopic ACTH is rarely reported, with only 6 cases described in the literature. 2,3 Hyponatraemia occurs frequently in hospitalised patients and is often underinvestigated. 4 Humayan et al demonstrated that hyponatraemia due to any cause but responsive only to tolvaptan was associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%